Editorial (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Three full years have passed since we took charge of the editorial team of the Latin American Journal of Sedimentology and Basin Analysis (LAJSBA). In July 2009 we set up a few objectives for the shortterm future of the journal and several things have happened since that we want to share with the community in order to analyse the future of LAJSBA. This inscribes not just in the relatively small universe in which the journal has impact but also in a fastevolving subject of scientific publications